Population genetics of the African wolf (Canis lupaster) across its range: first evidence of hybridization with domestic dogs in Africa - (:unkn) unknown (My University, 2020)
Despite the known genetic permeability among wolf-like canids, there is currently no evidence of gene flow between the recently acknowledged African wolf (Canis lupaster) and domestic dogs (C. lupus familiaris). We genotyped African wolves across their range, together with African domestic dogs and ‘reference’ grey wolves (C. l. lupus; not occurring in Africa). Northwestern African wolves showed (1) the greatest genetic diversity as observed from microsatellite loci and mitochondrial + Y-chromosome markers, and (2) possible signs of past admixture with grey wolves. We detected two zones of hybridization between domestic dogs and African wolves, in northwestern Senegal and central Ethiopia. Hybrids were intermediary in the nuclear genetic space separating African wolves from domestic dogs (and grey wolves), and were in majority assigned to domestic dogs in STRUCTURE. Hybrids showed mitochondrial DNA haplotypes of African wolves, suggesting gene flow directionality between male African dogs and female African wolves. The roaming of feral and shepherds’ dogs in degraded habitats occupied by African wolves may have promoted hybridization. Our results provide evidence that, subsequent to the possible hybrid origin of C. lupaster, the genome of the African wolf is still subject to admixture with C. lupus descendants. This could lead to the genetic dilution of endemic African wolf lineages, such as in eastern Africa, but may also imply disease prevalence and competition for resources with domestic dogs. Our study also is the first to show a significant level of differentiation (ΦST and FST) between North African and West African wolves. Wider genetic screening of African wolves across their range should depict more accurately their population dynamics and the potential stakes related to gene flow with domestic dogs.
Keywords: African Research